Seagrass community structure of Tayando-Tam Island, Southeast Moluccas, Indonesia - TYANI FITRIAN; AGUS KUSNADI; ROSMI NUSLAH PERSILETTE (Biodiversitas Journal of Biological Diversity, 2017)
Fitrian T, Kusnadi A, Persilette RN. 2017. Seagrass community structure of Tayando-Tam Island, Southeast Moluccas, Indonesia. Biodiversitas 18: 788-794. Seagrass bed is one of the marine ecosystem that having the highest productivity that could sustain coastal resources. The research purposes of this paper is to determine the community structure of seagrass at Tayando-Tam Island, Southeast Moluccas, Indonesia. The method of observation of seagrass bed using a line transect, transect ran perpendicular to the shore line for 100 meters. The field of observations include identification of seagrass species, counting the number of shoots and percentage (%) of seagrass cover. Seven species of seagrass had been found in Tayando-Tam island, i.e. Enhalus acoroides, Thalassia hemprichii, Cymodocea serrulata, Cymodocea rotundata, Halodule pinifolia, Halophila ovalis, Syringodium isoetifolium. Halodule pinifolia had the highest density in Tam Island with the number of 684.18 shoots/m2. The coverage in this area was between 4.64-43.1 %. Based on the number of species, diversity index and dominance index Tam Island had the most stable seagrass communities, with moderate value of diversity index (H'=1.26), high evenness Index (E=1.63), and low value of dominance index (D=0.34). Seagrass resources in the Tayando-Tam islands is good and the potential for biota the association, which is supported by the quality of water is good for the growth of seagrass.